Supply contracts, A comparative jurisprudential study - Alsulami, Abrar RizqAllah (Journal of Islamic Sciences, 2023)
Summary: this study aims to explain the rule of supply contracts in Islamic jurisprudence and its rooting, as it is one of the contracts introduced in our time and enters into all commercial and financial fields and contracting is common in all societies and countries in all its forms and names, but to what extent is it legitimate What is the ruling on dealing with them in Muslim societiesTherefore, this research came to explain these contracts and their ruling in Islamic jurisprudence.In this study, she dealt with the meaning of supply contracts, language, terminology and statement of their complex concept, stated their conditions and pillars, clarified their images and characteristics, quoted sayings in their adaptation and jurisprudence.Through this study, I concluded the following:- That supply contracts have various forms, some of which may resemble types of sales known before, such as: ladder, sale of the absent on the attribute, istisnaa. - Its judgment fluctuates between absolute permissibility or permissibility on the condition of one of the similar sales. - I also convey a different vision that combines the statements in its judgment.- The effects of the conclusion of supply contracts in the usual cases and circumstances, as well as in emergency circumstances, as happened in the corona pandemic and the accompanying preventive and precautionary measures.
Keywords: Supply; supply contracts rule; supply contracts; rooting of supply contracts; obligations in supply contracts